THE ASIATIC SPECIES OF PERSEA Mill. (Lauraceae) - Kostermans, A.J.G.H (Research Center for Biology, 1962)
The name Machilus was created by Rumphius (Herb. Amboin. 3: 70, 1743). The first post-Linnean description is of Desrousseaux in Lamarck, Encycl. 3:668. 1791, who, however, failed to indicate a type species (a Rumphian species) and as Machilus Rumphius consists of 4 different species belonging to 3 different genera, Machilus Desrousseauxis not acceptable as it is confusing.